EFEKTIVITAS PENERAPAN METODE MONTESSORI DALAM MENINGKATKAN KEMAMPUAN LITERASI AWAL KELOMPOK B DI TK BAHTERA BUKIT ZAITUN - Pattiwael, Elizabeth; Wiraswati, Anak Agung Ketut Sri; Utami, I Gusti Agung Ayu Yunita; Fauzi, Achmad (MANASA, 2024)
This quasi-experimental study assessed the effectiveness of the Montessori method on early literacy skills among Group B students at TK Bahtera Bukit Zaitun and compared outcomes with conventional teaching methods. The sample consisted of 28 students aged 5–6, divided into experimental and control groups. The Montessori apparatus included large movable alphabets, sandpaper letters, and reading boxes, with the study conducted from April to June 2024. Pretests and post-tests measured alphabet knowledge, phonemic awareness, and grapheme-phoneme correspondence. Results showed significant improvement in the experimental group, with median scores increasing from 2.5 to 3.8 and mode from 1.4 to 3.8. The Mann-Whitney U test yielded a p-value of .003, and the gain score analysis showed a p-value of 0.001 with a biserial rank coefficient of .7, confirming the Montessori method's effectiveness. It is recommended that kindergarten teachers incorporate phoneme-based approaches in literacy instruction, as these methods proved particularly helpful for students struggling with alphabet memorization.